Seleção de clones e produção de mudas de erva-mate por miniestaquia - Maculan, Luciane Grendene (2022)
Mate (Ilex paraguariensis St.-Hil.) is a native species of southern Brazil, with great economic, social, environmental and cultural importance where it occurs. Even that, there are no available technologies of asexual propagation necessary for the production of high-quality plantlets. Thus, the present work aimed at developing new mate clones and selecting those that combine high productivity of mini-cuttings and morphophysiological quality of plantlets by mini-cuttings. For the production of mate plantlets, a clonal mini-garden was established in a closed soilless cultivation system with coarse sand as substrate and flood fertigation. For rooting, mini-cuttings with approximately 2 cm in length were treated with 2000 mg L-1 of indolebutiric-acid and wee cultivated in polyethylene trays with 100 wells, containing commercial substrate based on pine bark, medium vermiculite and coarse sand (1 :1:1 v/v/v). After 60 days of cultivation in a humidity chamber, mini-cuttings were evaluated for percentage of survival and rooting, and number and length of the three largest roots. The daily current increment and the average daily increment were also calculated to determine the optimal permanence time of the mini-cuttings in the rooting environment. The rooted mini-cuttings were transferred to 280 cm3 tubes, containing a mixture of a commercial substrate based on pine bark and subsurface soil (2:1 v/v) to assess the morphophysiological quality of the plantlets. Mate plantlets were evaluated after 180 days of cultivation for survival percentage, number of leaves, shoot height (cm), collar diameter (mm) and the ratio between shoot height and diameter (cm/mm). The variance components were estimated based on repeated measures by the restricted maximum likelihood method (REML) and the prediction of phenotypic and genotypic values by the best linear unbiased prediction (BLUP). The experiment was carried out in a complete random design, with different number of experimental units. The optimal time for the mini-cuttings to remain in a humid chamber ranged from 28 to 63 days, depending on the clone. Clonal differences were found for percentage of rooting, number of roots and number of leaves. Four mate clones that combine rooting competence and plantlet quality were selected, resulting in selection gains for rooting percentage (43.5%), number of roots (15.8%), and number of leaves (15.1%). High gains from selection indicate the feasibility of this genetic improvement strategy for the development of mate clones for asexual propagation by mini-cuttings.